Malaysia Economic Monitor, June 2020 : Surviving the Storm - World Bank (World Bank, Washington, DC, 2020)
Malaysia's economy has been severely affected by the COVID-19 (coronavirus) pandemic. In 2020, Malaysia's economy is projected to contract by 3.1 percent. In Q1 2020, growth slowed to just 0.7 percent with efforts to flatten the curve of the pandemic through a series of movement control orders and with deep uncertainty regarding growth prospects severely constraining economic activity. A pronounced output contraction of around 10 percent in Q2 2020 is envisioned, reflecting the significant impact of the economic disruptions resulting from the MCO imposed during the quarter. This is expected to be followed by a partial recovery in the second half of the year, as the outbreak eases and mobility restrictions are gradually lifted. This forecast assumes that the spread of pandemic is broadly contained at the global level and that the massive fiscal and monetary policy support measures implemented by governments around the world limit the depth of contraction to global economic activity. With all these factors, the near-term outlook for Malaysia's economy is unusually uncertain at present. The COVID-19 pandemic has resulted in an unprecedented crisis that requires large-scale and unconventional policy responses by governments everywhere. With the crisis severely affecting private demand and causing supply shocks, the government is tasked with the responsibility of facilitating economic recovery in the near term. Malaysia's economy remains resilient and rests on strong fundamentals. Its diversified economic structure, sound financial system, effective public health response and proactive macroeconomic policy support suggest that Malaysia will be able to ride out the storm better than many other countries. In the near term, Malaysia's fiscal strategy should be re-prioritized to create additional policy space. This will require efforts to re-allocate expenditures towards priority areas, identify new sources of nontax revenue, as well as legislative amendments to temporarily increase available fiscal space.